Inter-annual variability of biogeography-based phytoplankton seasonality in the Arabian Sea during 1998–2017. (June 2022) - Huang, Ke; Xue, Huijie; Chai, Fei; Wang, Dongxiao; Xiu, Peng; Xie, Qiang; Wu, Ying; Liao, Xiaomei; Ma, Wentao; Yao, Jinglong; Zhou, Wei
Abstract: Long-term multi-satellite-based DINEOF-reconstructed chlorophyll- a data are utilized to generate an updated biogeography of phytoplankton seasonality and to decipher the environmental controls in the Arabian Sea (AS). As in published information, the biogeographical clusters and biological boundary of phytoplankton seasonality are mostly organized and stable in four separated provinces, but also suffering significant yearly biogeographical discrepancies. Four distinct clusters are identified that correspond to the summer-peak upwelling cluster (17.5% of AS area), winter-peak entrainment cluster (17.4%), tropical flat cluster (33.7%), and transitional cluster (31.4%), appearing regularly in the AS with their boundaries tightly linked to the coast lines. Considerable inter-annual variability of the biogeography of seasonality is evident with a significant instability that occurred in the interior AS. The biogeographical shifts observed are in agreement with surface advection, upwelling-favorable wind and wind-induced entrainment anomalies. Inﬂuences of wind mixing power on the distribution of summer-peak/transitional taxa of the central AS in 2006/2009/2016 are hypothesized. The most spatial changes of the summer-peak clusters in 2015 and 2016 are strongly linked to the co-occurred extreme positive and negative IOD&ENSO events. The IOD-/ENSO-related wind-induced Ekman transport and local/remote forced upwelling Rossby waves are consolidated and combined to generate the observed unprecedented biogeographical variability in the southern tip of India in 2015 and 2016.